Implementation of Inclusive Education for Students with Special Needs in Public Schools: A Qualitative Study - Sutrisno; Alberto Briganti (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This article examines the implementation of inclusive education in public schools through interviews with teachers, parents, and students with special needs. The study finds that despite the adoption of inclusive policies, challenges remain in terms of resources, teacher training, and social acceptance within the school environment. Using a qualitative approach, data were collected through in-depth interviews with 15 teachers, 10 parents, and 5 students with special needs in public schools in Indonesia. The findings highlight that while inclusive education promotes equal learning opportunities, the lack of adequate support systems, specialized teaching strategies, and societal awareness hinders its effectiveness. Teachers struggle with adapting curricula and managing diverse learning needs due to insufficient training and resources. Parents express mixed perspectives regarding the success of inclusion, citing both benefits and concerns about their children's academic and social development. Meanwhile, students with special needs often face difficulties in peer interactions and classroom participation. This study underscores the importance of comprehensive policy support, professional development for educators, and collaborative efforts between schools, families, and communities to enhance the effectiveness of inclusive education.